Constructing ethnic identity in 1 Peter: who you are no longer - Ok, Janette H. (Library of New Testament studies, 2021)
Cover -- Contents -- Acknowledgments -- Abbreviations -- 1 Introduction: What Do Ethnicity and Identity Have to Do with 1 Peter? -- Defining the Terms -- Ethnic-Religious Composition -- Conclusion -- 2 Defining and Defying Ethnicity in the Ancient World -- Introduction -- Framing the Study of Greek Ethnic Identity -- The Emergence of Panhellenism and the Concept of the Barbarian -- Imagining Persia and Constructing Greekness -- The Proof Is in the Stock: Defining Greek Ethnicity -- Greek Ethnicity under Roman Rule -- Rome's Civilizing Mission -- Remaining Greek while Becoming Roman -- Conclusion -- 3 Common Blood: Establishing a New Patrilineage through the Blood of Christ -- Introduction -- Establishing God as Father -- "As Obedient Children" -- Connecting New Birth with Christ's Ransoming Blood -- Employing the Logic of Patrilineal Descent -- Not Sons, but Children of God -- Appropriating Israel's Identity-Defining Designations for a Dislocated People -- Elected Group Identity -- Conclusion -- 4 Constructing Boundaries and Contesting Stigma in the Making of Ethnic Identity in 1 Peter -- Introduction -- Barth on Ethnic Boundaries -- Constructing Social Boundaries in 1 Peter -- Disidentifying from "The Futile Conduct Inherited from Your Ancestors" -- Constrained Christian Identity -- Construing the Gentile "Other" -- Goffman on Stigma -- Contesting and Subverting Christian Stigma in 1 Peter -- "Faith Information Control" -- Stigma Reversal -- Honorary Ethnics -- Conclusion -- 5 Conclusion: Reinforcing Christian Distinctiveness through Bonds of Blood -- Further Implications of This Study -- Asian American Studies -- Canonical Studies -- Bibliography -- Scripture Index -- Subject Index.